Animals in ritual and economy in a Roman frontier community : excavations in Tiel-Passewaaij - Groot, Maaike (Amsterdam archaeological studies, 2008)
This new volume in the acclaimed Amsterdam Archaeological Studies series explores the roles of animals in a rural community in the civitas Batavorum.